2017
DOI: 10.14796/jwmm.c414
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Calibration

Abstract: Generally, event based rainfall-runoff model calibration and verification is a laborious and expensive activity. With the availability of long term continuous flow meter and rainfall data and faster computers and software, models can now be calibrated to a long term flow record spanning from few months to several years. The practice of model calibration for large and complex regional systems is evolving over the years away from the conventional event based two step calibration and verification process to a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The Nash-Sutcliffe efficiency index is a commonly used performance indicator, although the upper benchmark for acceptable performance seems to vary from as low as 0.5 up to 0.75 (Lin et al 2017;Seibert et al 2018;Lane et al 2019). Shamsi and Koran (2017) recommended that a Nash-Sutcliffe value in the range 0.5-1.0 could be considered an excellent calibration result and as such, the model could be used for planning, preliminary designs, and final designs. Shamsi and Koran (2017) further suggested that ISE classifications of model calibration in the Very Good and Excellent categories could be used for planning, preliminary designs, and final designs, while model calibration achieving an ISE Good rating could be used for planning and preliminary designs.…”
Section: Discussionmentioning
confidence: 99%
“…The Nash-Sutcliffe efficiency index is a commonly used performance indicator, although the upper benchmark for acceptable performance seems to vary from as low as 0.5 up to 0.75 (Lin et al 2017;Seibert et al 2018;Lane et al 2019). Shamsi and Koran (2017) recommended that a Nash-Sutcliffe value in the range 0.5-1.0 could be considered an excellent calibration result and as such, the model could be used for planning, preliminary designs, and final designs. Shamsi and Koran (2017) further suggested that ISE classifications of model calibration in the Very Good and Excellent categories could be used for planning, preliminary designs, and final designs, while model calibration achieving an ISE Good rating could be used for planning and preliminary designs.…”
Section: Discussionmentioning
confidence: 99%
“…The model was calibrated and then validated using existing stream gauge data at the four gauges available for use, alongside the three rain gauges that cover the watershed. The model was simulated using the "continuous simulation" process as advocated by Shamsi and Koran [8]. This process is more challenging than event-based hydrologic rainfall-runoff models due to longer calibration and validation periods.…”
Section: Methodsmentioning
confidence: 99%
“…This guidance document suggests matching water mass budgets at ±10% for dry periods and −10% to +20% for wet periods. Other researchers suggest the appropriate range of NSE coefficients for planning purposes and preliminary design to be at least 0.30 to 0.39 [8]. Values greater than 0.5 are considered "excellent" for calibration purposes, permitting even final design use of the model.…”
mentioning
confidence: 99%
“…There are multiple studies and documents that support the idea that in the case of rainfall-runoff models it is significantly more accurate to simulate over the entire time series available for model calibration; thus, a continuous calibration was completed rather than single event based (James 2005, Rosa et al 2015, Shamsi and Koran 2017.…”
Section: Calibration and Validationmentioning
confidence: 99%